Rapid bioassessment of the ecological integrity of the Lourens, Palmiet and Hout Bay Rivers (South Western Cape, South Africa) using aquatic macroinvertebrates - Ollis, Dean Justin (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2005.